Ma’had Aly sebagai Fenomena Nasional:: Kaderisasi Ulama, Otoritas, dan Politik Prestise Pesantren - muhammad yusuf_marjani; Amir Maliki Abitolkha; Arhan; Mim Maulana Mubarok (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2026)
ABSTRACT The emergence and growth of Ma’had Aly as a pesantren-based higher education institution mark a significant transformation of Islamic education in contemporary Indonesia. This article analyzes Ma’had Aly as a national phenomenon through five dimensions: institutional growth, state policy, ulama cadre formation, transformation of religious authority, and the politics of pesantren prestige. Employing a qualitative library research approach framed by the sociology of knowledge—Max Weber’s theory of authority, Pierre Bourdieu’s symbolic capital, and Talal Asad’s discursive tradition—data were drawn from government regulations, Ministry of Religious Affairs statistics, and academic literature. The findings show that Ma’had Aly expanded from 27 institutions in 2017 to 91 institutions by March 2025. Beyond functioning as an institution for ulama cadre formation, Ma’had Aly operates as a mechanism for the institutionalization of religious authority and the reproduction of pesantren symbolic capital. Its establishment reflects pesantren responses to modernity while simultaneously becoming an arena of prestige contestation within the national socio-religious field. The novelty of this study lies in synthesizing Weber–Bourdieu–Asad to explain Ma’had Aly as both a cadreization project and an arena of symbolic struggle.  Keywords : Ma’had Aly, Religious Authority, Symbolic Capital, Pesantren, Islamic Higher Education